Pengaruh Pemberian Asiklovir dalam Menurunkan Progresifitas dan Transmisi HIV - M Rafli Febri Asshiddiq (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: The HIV / AIDS epidemic presents severe challenges for development and social progress. HIV is a virus that is transmitted mainly through sexual contact, intravenous lines that are used together, and mother to child transmission that can occur during the process of birth or breastfeeding. HIV is mainly caused by infection with HIV-1 or HIV-2, a retrovirus of the family retroviridae, genus Lentivirus. Treatment with anti-retroviral therapy has been effective and has helped to maintain health for those with HIV infection but HIV-related mortality rates remain high. Prevention efforts are made to reduce mortality and morbidity related to HIV. One of the prevention efforts that can be done is using acyclovir but this is still controversial. Acyclovir is an agent used to treat infections caused by the herpes simplex virus (HSV). Objective: To determine the role of acyclovir in reducing transmission of HIV transmission. Method: Using literature studies from both nationally and internationally journal by summarizing the topic of discussion and comparing the results presented in the article. Results : HIV coinfection with HSV can increase transmission and disease progression. The main treatment for herpes simplex is with acyclovir. Acyclovir at a dose of 2x400 mg and valacyclovir at a dose of 2 x 500 mg reduce the progression of the disease. Acyclovir has a direct anti-HIV effect. But acyclovir does not reduce transmission from HIV itself. Conclusion: Acyclovir plays a role in reducing mortality and the progression of HIV to AIDS with direct anti-HIV effects.